Development of physical fitness of students based on new pedagogical technologies - Khasanov A.T; Azimov A.M (Zien Journals, 2023)
The article presents the results of a pedagogical experiment and their analysis in order to develop methodological recommendations aimed at further improving the professionally applied motor training of students, with an emphasis on professionally applied physical training
Keywords: Motor fitness; volume of loads; physical qualities; professional and applied physical training